Anthropometric and physiological indicator prospects of professional growth of weightlifters - Chernogorov, D.; Matveev, Y.; Sivokhin, I.; Ogandzhanova, A. (Journal of Physical Education and Sport, 2021)
The purpose of this study was to determine the ratio of the training load performed during the pre-competition period of training weightlifters, depending on the type of physique. Materials and methods: A total of 16 men and 10 women involved in weightlifting at the Olympic Reserve Sports School participated in this study. The following methods were used: the method of anthropometry (height-weight and girth dimensions), analysis of the results of photo-video recording (asymmetry of projectile lifting - front view); analysis of the diaries of the performed load (parameters of the volume and intensity of the training load, the number of exercises); mathematical data processing. Results: A comparison of the obtained data shows that during the pre-competitive mesocycle of training, athletes with a normal physique ("mesomorphic" type), in comparison with athletes with other body types, performed a load of higher intensity but smaller volume, with fewer approaches per workout to achieve the planned results. In athletes with a "brachymorphic" body type, this indicator was lower by more than 1% and amounted to 94.3% for men and 93.1% for women. The lowest average monthly intensity was found in athletes with a "dolichomorphic" body type - 86.5% in men and 87.1% in women. Unlike athletes with the described normal physique, athletes with a lean physique had an average monthly intensity of training load for exercises developing leg strength, which was lower in both men and women (by 10% and 8%, respectively), but on average higher in the number of exercises (4.8 ± 1.1 for men and 4.5 ± 0.9 for women). According to this indicator, athletes with a "brachymorphic" body type required a greater amount of training work (5.2 ± 0.8 for men and 5.3 ± 1.1 for women).